Mechanistic origin of the stereodivergence in decarboxylative allylation - Chattopadhyay, Kalicharan (2010)
[Image: see text] A stereochemical test has been used to probe the mechanism of decarboxylative allylation. This probe suggests that the mechanism of DcA reactions can change based on the substitution pattern at the α-carbon of the nucleophile, however reaction via stabilized malonate nucleophiles is the lower energy pathway. Lastly, this mechanistic proposal has predictive power and can be used to explain chemoselectivities in decarboxylative reactions that were previously confounding.